Co si mohou nabídnout queer a feministická teorie. (Marinucci, M. Feminism is Queer) - Blanka Nyklová (Gender a Výzkum)
Book review of Marinucci, Mimi. 2010. Feminism is Queer. The intimate connection between queer and feminist theory. London: Zed Books.